Metal consumption rates in rolling production - S. A. Kashko (Литьë и металлургия)
The rationing of material resources is understood as the process of determining the amount of their consumption necessary for the normal production process. The regulatory framework includes a set of norms and standards applied at the enterprise for planning and analytical purposes. The consumption rate is the maximum permitted planned amount of raw materials, materials for the production of a unit of production (work) of established quality in the planned production conditions. The consumption standard is the specific consumption of raw materials or materials attributed to a unit of mass, area, length, volume, which is a component of the consumption standards. The multidimensional nature of technological processes, as well as the multidirectional application of consumption standards determine their classification by the degree of enlargement of the object of rationing (individual; group); by the degree of enlargement of the nomenclature of materials (specific in the nomenclature for production; consolidated for homogeneous types of raw materials, materials for the production of a product or a nomenclature group of products); period of validity. This article presents methods for calculating individual specific metal consumption rates in the production of rolled products at the rolling mill 370/150 of OJSC «BSW – Management Company of Holding «BMC».